SYNTAXOMOMICAL SURVEY O F EUROPEAN BEECH FORESTS: SOME GENERAL CONCLUSIONS - DIERSCHKE, H. (Annali di Botanica, 1997)
A short overwiev is given about the historical development of syntaxonomy of European beech forests. Different solutions of classification have been proposed, following more or less two main approaches: Division of alliances and suballiances by ecologically or geographically orientated species groups. A new classification of European beech forests is proposed with 8 (or more) geographically orientated alliances, which can be further divided into suballiances by ecological species groups. For each alliance character and differential species, nomenclatural type and the area is mentioned, based on a (non puplished) synthetic table, including 10.006 relevés from all parts of Europe. From this table also some overlapping species groups (a-n) are given.